Land use change in tropical watersheds : evidence, causes and remedies (CABI, 2005)
This book studies land use change in tropical landscapes, with particular emphasis on the economic processes that influence rates of land degradation and forest clearing. Multidisciplinary contributions draw lessons from data collected between 1992 and 2004 in the Manupali watershed in southern Philippines. Through this detailed case study, the book documents forces leading to land use changes, in particular the potential impacts of institutional evolution and policy reforms, and highlights interrelationships among biological, economic, and social phenomena. This book will be of interest to those studying natural resource economics, soil and water conservation, land use, and agricultural development. The book has 12 chapters and a subject index.